Prevalence Of Cryptosporidiosis In Calves And Child In Al Diwania City: Alaa mohammed abdul razak ** Ghaidaa abas Jasm - Jasm, Ghaidaa abas (The Iraqi Journal of Veterinary Medicine, 2011)
The aim of study to investigate of Cryptosporidium parum Parasite 200 faecal samples were collected from cattle in different age from abattoir and hospital of veterinary and infants in children and maternity of Al–Diwania Governorate and examined by Modified acid fast staining .The prevalence and intensity of cryptosporidiosis was found more in adult calves ( 44% ) in diarrheic group and 12% in non diarrheic group and the percentage was different from the other age group. While in Infant 17.5% were positive from diarrheic group and 8.3% in nondiarrheic group in 2-4 years old and the percentage was different from the other age group according the site of live in rural and urban community . This study was conclude that the age and present or absence of diarrhea significant differences in severity of infection with Cryptosporidium parum .